Antimicrobial activity of cell-free supernatant derived from Ligilactobacillus animalis SWLA-1 in a novel ex vivo canine corneal infection model - Jang, Je-Hwan; Lee, Hong-Jae; Kim, Dong-Hwi; Lee, Sang-Won; Kim, Joon-Young (Frontiers in Veterinary Science, 2024)
Canine bacterial keratitis is a corneal infection that causes various symptoms, including visual impairment, and necessitates eye removal in severe cases. Staphylococcus pseudintermedius is a pathogen that causes significant bacterial keratitis in canine patients. Moreover, multi-drug resistant Staphylococcus pseudintermedius (MDRSP) has been reported in both humans and animals. Regarding treatment failure against multi-drug resistant (MDR) pathogens with classic antibiotics, antimicrobial compounds derived from probiotics have been suggested as an alternative approach. Ligilactobacillus animalis SWLA-1 strain and its cell-free supernatant (CFS) have previously demonstrated potent antimicrobial activity against various MDR pathogenic bacteria. Based on this finding, we evaluated the anti-staphylococcal activity of CFS derived from Ligilactobacillus animalis SWLA-1 against MDRSP in a newly established ex vivo canine corneal infection model using fresh canine corneoscleral rims. Additionally, an in vitro cytotoxicity test using human keratocytes was performed. CFS significantly inhibited the growth of MDRSP in the novel ex vivo model and did not exhibit any significant toxicity against keratocytes in vitro. Based on these results, the antimicrobial compounds in CFS show potential as a novel approach for MDR staphylococcal keratitis treatment.